2020
DOI: 10.1038/s41598-020-69195-5
|View full text |Cite
|
Sign up to set email alerts
|

Biases in estimation of insect herbivory from herbarium specimens

Abstract: information regarding plant damage by insects in the past is essential to explore impacts of climate change on herbivory. We asked whether insect herbivory measured from herbarium specimens reflects the levels of herbivory occurring in nature at the time of herbarium sampling. We compared herbivory measurements between herbarium specimens collected by botany students and ecological samples collected simultaneously by the authors by a method that minimized unconscious biases, and asked herbarium curators to sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…However, contrary to expectations, we did not discover any temporal shift in the aesthetic value of herbarium specimens. This finding suggests that, as in the case of selectivity with respect to insect damage ( Kozlov et al , 2020 ), the importance of aesthetic reasons varied among collectors, and this variation appeared much greater than the temporal shift in the importance of aesthetic reasons in the selection and preparation of herbarium specimens. The importance of aesthetic reasons can also depend on external circumstances and would be lower in specimens collected during short-term excursions to remote localities than in specimens sampled next to a botanist’s home.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…However, contrary to expectations, we did not discover any temporal shift in the aesthetic value of herbarium specimens. This finding suggests that, as in the case of selectivity with respect to insect damage ( Kozlov et al , 2020 ), the importance of aesthetic reasons varied among collectors, and this variation appeared much greater than the temporal shift in the importance of aesthetic reasons in the selection and preparation of herbarium specimens. The importance of aesthetic reasons can also depend on external circumstances and would be lower in specimens collected during short-term excursions to remote localities than in specimens sampled next to a botanist’s home.…”
Section: Discussionmentioning
confidence: 89%
“…The substantial increase in the number of leaves in herbarium specimens between 1558 and 2016 may also have affected the levels of insect herbivory measured from these specimens. Botanists have always been advised to collect specimens that bear no or few signs of damage ( Greville, 1840 ; Bailey, 1899 ; Pearsall, 2015 ), and an earlier study demonstrated that both collectors and curators generally preferred specimens with less leaf damage ( Kozlov et al , 2020 ). Obviously, finding a large (50‒100 leaves) branch with no or minor leaf damage is more challenging than selecting a small (5‒15 leaves) branch with no traces of insect feeding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… Summary Kozlov and colleagues 1 call into question the application of herbarium specimens to quantify historical patterns of herbivory 25 . It is already widely appreciated that collectors of herbarium specimens may tend to avoid insect damage, thus making herbivory estimates from herbarium specimens potentially down-biased 2 .…”
mentioning
confidence: 99%